Microsite-Based E-Learning as an Adaptive Pedagogical Tool: Enhancing Student Mastery of Rukhsah Concepts - Pratama, Farandika Nanda; Nusaibah, Nusaibah; Arliansyah, Ihsanul Hudiya (FKIP Universitas Lampung, 2025)
Microsite-Based E-Learning as an Adaptive Pedagogical Tool: Enhancing Student Mastery of Rukhsah Concepts. Objective: Learning activities during the day and the insufficiency of the media used are obstacles for Islamic Religious Education (PAI) educators at SMP 1 Kudus, leading to low student attention and affecting students’ mastery of the learning material. This article presents a novelty: the development of e-learning media based on Microsite S.Id. as an innovative, interactive, and aligned solution with the Merdeka Curriculum. Methods: The purpose of this article is to describe the development process, the media's feasibility, and its potential to enhance students’ mastery of the Rukhsah concept. This research utilized the R&D method with the ADDIE model, involving 27 seventh-grade students at SMP 1 Kudus, Indonesia, and experts as validators. Data collection techniques included tests (pre-test and post-test) and non-tests (questionnaires, observations, interviews, and documentation). Findings: The media is classified as “Very Feasible” across the aspects of materials, media, teaching modules, and assessment. The results of concept mastery tests through the Wilcoxon Test showed a significance value of 0.000 (<0.05), along with an N-Gain Score of 0.8793 and an N-Gain Percent of 87.93%, which are categorized as “High” and “Very Effective.